Amazonas Academic League for Rare Diseases as a tool for knowledge and dissemination of rare diseases: Experience report (Research, Society and Development, 2024)
Academic leagues are university extension project activities aimed at complementing academic training. In that regard, the Amazonas Academic League of Rare Diseases emerged with the aim of bringing to academics at the Federal University of Amazonas, Manaus and Coari campuses, knowledge and dissemination of information about rare diseases. The objective was to report the process of activities carried out by the Amazonas Academic League for Rare Diseases. Research was carried out with a descriptive, qualitative approach of the experience report type. LADORAM was founded in 2022 and is linked to the Federal University of Amazonas. LADORAM has academic leaders from Medicine, Biological Sciences, Biotechnology, Nursing and Nutrition and professors from the areas of Genetics, Cellular and Molecular Biology and Pediatrics as well as doctors from different specialized areas. Everyone participated in meetings via Google Meet to present seminars on rare diseases. There were publications of simple and expanded summaries and the implementation of various actions. Therefore, the activities carried out and experienced by LADORAM were essential for disseminating and raising awareness about rare diseases, as well as providing early contact with rare diseases, in order to understand the proportions they reach. In this way, they brought benefits to academics by sharing knowledge in a critical and responsible way.